Safety of same day discharge after atrial fibrillation ablation. (3rd October 2022) - Ijaz, H; Al-Sadawi, M; Aslam, F; Aleem, S; Jacob, R; Cao, K; Santore, L; Almasry, I; Singh, A; Fan, R; Rashba, E
Abstract: Background: Atrial fibrillation (AF) ablation is an outpatient procedure with traditionally an overnight hospital observation (OHO). Recently, there has been a trend towards same day discharge (SDD). Purpose: Compare AF ablation procedure safety outcomes with SDD vs. OHO. Methods: We reviewed consecutive AF procedures performed from January 2013 to June 2021 at a single academic center. Patients underwent OHO until June 2020, after which patients had SDD whenever feasible. Adverse events were assessed at three months, which included pericardial effusion, pericarditis, post-procedure hypotension, embolic events, and vascular complications. We also assessed emergency department (ED) visits and procedure-related hospital admissions. Results: There were 1254 patients who underwent 1575 AF ablations. 1440 patients underwent OHO and 135 had SDD. Mean age was 62.2 years, BMI 33 kg/m 2, 65% were male, and 27.6% had persistent AF, without significant differences in baseline characteristics between OHO and SDD. We found that SDD was not associated with increased complications (OHO 0.20% v. SDD 0.49%; p>0.05), ED visits, or hospital admissions (2% v. 5%; p>0.05) (Figure 1, 2). There were no gender or age-related disparities in all outcomes (p>0.05). Conclusion: SDD protocol after AF ablation is feasible and not associated with higher incidence of complications, ED visits, and procedure-related hospitalizations. Funding Acknowledgement: Type of funding sources: None.